Immigration and Prices - Saul Lach (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2005)
This paper exploits the unexpected arrival of 200,000 FSU immigrants to Israel during 1990 to empirically examine the effect of a change in demand on prices. The main finding is that immigration had a moderating effect on prices during 1990. Controlling for the selection of immigrants into cities and for population growth, a 1 percentage point increase in the share of immigrants in a city decreases prices by about 1.4-1.8 percent. Even when the increase in population is accounted for, the overall effect of immigration on prices remains negative. This downward effect on prices is stronger in products where demand increases are larger. The negative immigration effect can be explained by the new immigrants searching more intensively for lower prices than the native population. In support of this interpretation, it is shown that the relationship between price dispersion across stores and the share of immigrants has an inverse-U shape as implied by Stahl's (1989) model of search.
Keywords: 330